A STUDY ON SHOPPER’S EXPERIENCE IN SHOPPING MALL BASED ON THE SERVICE QUALITY FACTORS - Eapen Thomas, Felix; Siji, Smitha (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
In the modern world, shopping has become an essential routine for the people living in our country. Shopping mall is viewed not only as a purchasing centre but also as an area for the people to get together, socialize as well as for finding entertainment, etc. Since, a transition can be noticed from the traditional shopping centre to an area of community engagement, the proposed study focuses on understanding various service quality factors offered by the shopping mall and also its implications. The paper also investigates the demographic nature of the respondents where the significance between each group is taken into consideration. The structural equation modelling analysis provides important insights to understanding the impacts of different quality components on shopping experiences across. Based on the test performed, it is found out that all the three independent variables are having a positive impact on the shopper’s response and also the demographic study states that there is a significant difference in the shopper’s response across the different age groups. Keywords: Service Quality, Shoppers Response and Personal Attention